Unveiling Educational Frontiers: Exploring The Role Of Filipino Language In Higher Learning (Journal of Namibian Studies : History Politics Culture, 2022)
This study delves into the significance of incorporating the Filipino language within higher education. The research aims to uncover new perspectives in the educational landscape by examining the role and impact of the Filipino language in tertiary curricula. Through comprehensive analysis and interpretation of data, the study investigates how the inclusion of Filipino language influences teaching methods, learning outcomes, and overall educational experiences. By exploring this uncharted territory, the research contributes to the ongoing discourse on language diversity and its implications for higher learning institutions. Ultimately, this study fosters a deeper understanding of the multifaceted benefits that arise from integrating the Filipino language, enriching the educational journey for both students and educators alike. Based on the research findings, it is concluded that the incorporation of the Filipino language significantly enhances college students' comprehension and navigation of intricate subjects in the curriculum that demand higher-order cognitive skills. This underscores the importance of integrating modern teaching methodologies and technologies to effectively engage students with the Filipino language, particularly when dealing with complex real-life scenarios. Teaching Filipino assumes a pivotal role in national development, aligning with the constitutional designation of Filipino as the official language for national identity and needs. Given linguists' assertion that Filipino is comparatively easier to learn than foreign languages, its widespread use is crucial for fostering unity among Filipinos. Prioritizing our own language, a key emblem of our identity, becomes pivotal in presenting the Philippines as a distinct nation within the global community. Drawing from the study's findings and conclusions, the researcher recommends that customized training strategies should be employed with diverse training approaches tailored to students' specific fields of study, maximizing the value of their learning experience in the Filipino subject. Recognizing varying intellectual capacities, instructors should facilitate the attainment of learning objectives while keeping students engaged. Tertiary level administrators can leverage these findings to shape curriculum guidelines and institutional policies that empower educators to effectively teach the Filipino language. This includes equipping them with the necessary skills and resources. By implementing these recommendations, educational institutions can better equip students to navigate complex subjects and foster a stronger connection to their national identity through the Filipino language.